FEATURES OF DIFFRACTION FOCUSING OF A SPHERICAL X-RAY WAVE ON A SHORT PERIOD SUPERLATTICE - Levonyan, L.V.; Manukyan, H.M. (Proceedings of the YSU A: Physical and Mathematical Sciences, 2017)
The problem of a dynamic diffraction of spherical X-ray wave on a short period superlattice is considered theoretically. It is shown that a focusing of satellites occurred both at different depths of the superlattice and at different distances from the crystal in vacuum depending on the structural factors of the superlattice. The larger the structural factor of the satellite, the more deeply the wave in the crystal is focused and, respectively, the less is the focal length out of the crystal in vacuum.